The Impact of the Inauguration of 2nd Reshuffled Cabinet on LQ-45 Stock Prices - Hatmanti, Aulia; Sudibyo, Bambang (Jurnal Economia, 2017)
Abstract: The Impact of the Inauguration of 2nd Reshuffled Cabinet on LQ-45 Stock Prices. The purpose of this research is to observe the impact of the political event the inauguration of 2nd reshuffled cabinet-to LQ-45 group’s stock prices. This study used event study method to identify the market reaction that can be seen from the abnormal return on the stock prices. The abnormal return is calculated using mean-adjusted model. T-test indicates that there is a significant positive abnormal return on event day (t) and t+3. Besides, paired sample t-test was conducted to see the difference in the average abnormal return in 5 days before and five days after the events didn’t show any significant results. Based on these results, it can be concluded that the inauguration of 2nd reshuffled cabinet is good news for investors. Keywords: event study, abnormal return, LQ-45, political eventsAbstrak: Pengaruh Pelantikan Kabinet Kerja Hasil Reshuffle Jilid II terhadap Harga Saham LQ-45. Tujuan dari penelitian ini adalah untuk melihat pengaruh peristiwa politik-pelantikan Kabinet Kerja hasil reshuffle jilid II-terhadap harga saham yang terdaftar dalam kelompok saham LQ-45. Penelitian ini menggunakan metode studi peristiwa untuk melihat adanya reaksi pasar yang dapat dilihat dari adanya abnormal return pada saham. Abnormal return pada penelitian ini dihitung menggunakan mean-adjusted model. Berdasarkan hasil uji beda t-test satu sisi, terdapat abnormal return positif yang signifikan pada event day (t) dan t+3. Uji beda rata-rata menggunakan paired sample t-test yang dilakukan untuk melihat perbedaan rata-rata abnormal return pada 5 hari sebelum dan 5 hari sesudah peristiwa tidak menunjukkan adanya hasil yang signifikan. Berdasarkan hasil tersebut, dapat disimpulkan bahwa peristiwa politik berupa pelantikan Kabinet Kerja hasil reshuffle jilid II merupakan good news bagi investor. Kata kunci: studi peristiwa, abnormal return, LQ-45, peristiwa politik